2010
DOI: 10.3171/2010.8.peds08491
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendoscopic treatment of arachnoid cysts of the quadrigeminal cistern: a series of 14 cases

Abstract: Object In this paper, the authors' goal was to evaluate the role of neuroendoscopy in the treatment of arachnoid cysts of the quadrigeminal cistern. Methods Between March 1995 and February 2008, 14 patients affected by arachnoid cysts of the quadrigeminal cistern were treated endoscopically. The cysts were classified according to their anatomical and radiological appearance. The most frequent form (Type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 22 publications
0
52
0
1
Order By: Relevance
“…According to Almeida et al, 79 cases were reported in the literature up to 2008 [2]. A Pubmed search revealed 38 new cases since then [5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Almeida et al, 79 cases were reported in the literature up to 2008 [2]. A Pubmed search revealed 38 new cases since then [5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…With the extent of the indications for ventricular endoscopy, the neuroendoscopic approach to quadrigeminal cysts has gained increasing acceptance. Several authors have reported cases [1,4,5,[9][10][11][12][15][16][17][18][19][20] or series [3,5,13] of neuroendoscopic quadrigeminal cyst treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying treatment goal is to drain or divert the contained CSF within the arachnoid cyst. The described approaches include stereotactic aspiration, craniotomy with excision of cyst, cyst fenestration, cystocisternostomy, ventriculocystostomy, and cystoperitoneal shunting [87]. Recent advances in neuroendoscopy have resulted in most of the arachnoid cysts being treated with endoscopic fenestration [88,89].…”
Section: Arachnoid Cystsmentioning
confidence: 99%
“…These endoscopic approaches have been modified by burr hole location and use of stereotaxy to allow for fenestration of quadrigeminal [87,90], suprasellar [75,[91][92][93][94], middle fossa [79], prepontine [95], interhemispheric [96], retroclival [97], and third ventricular arachnoid cysts [94] with satisfactory outcomes.…”
Section: Arachnoid Cystsmentioning
confidence: 99%
See 1 more Smart Citation